2019
DOI: 10.1098/rspb.2019.2426
|View full text |Cite
|
Sign up to set email alerts
|

Ordered phylogenomic subsampling enables diagnosis of systematic errors in the placement of the enigmatic arachnid order Palpigradi

Abstract: The miniaturized arachnid order Palpigradi has ambiguous phylogenetic affinities owing to its odd combination of plesiomorphic and derived morphological traits. This lineage has never been sampled in phylogenomic datasets because of the small body size and fragility of most species, a sampling gap of immediate concern to recent disputes over arachnid monophyly. To redress this gap, we sampled a population of the cave-inhabiting species Eukoenenia spelaea from Slovakia and inferred its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 31 publications
4
80
0
2
Order By: Relevance
“…DNA was extracted using the Qiagen DNeasy Blood and Tissue Kit (Valencia, CA) from one to five specimens, prioritizing tissue from the propodus and main claw (gut-free leg podomeres) where possible. Taxonomic sampling consisted of 89 sea spiders; outgroups consisted of 14 Arachnida (including one Xiphosura, which has recently been shown to be possibly nested within the arachnids; Ballesteros and Sharma 2019 ; Ballesteros et al. 2019 ), 3 Myriapoda, 3 Pancrustacea, and 1 Onychophora.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted using the Qiagen DNeasy Blood and Tissue Kit (Valencia, CA) from one to five specimens, prioritizing tissue from the propodus and main claw (gut-free leg podomeres) where possible. Taxonomic sampling consisted of 89 sea spiders; outgroups consisted of 14 Arachnida (including one Xiphosura, which has recently been shown to be possibly nested within the arachnids; Ballesteros and Sharma 2019 ; Ballesteros et al. 2019 ), 3 Myriapoda, 3 Pancrustacea, and 1 Onychophora.…”
Section: Methodsmentioning
confidence: 99%
“…A list of taxa sampled from field expeditions, museum collections, and multiple deep sea cruises is provided as electronic supplementary material, table S1. Taxonomic sampling consisted of 89 sea spiders; outgroups consisted of 14 Arachnida (including one Xiphosura, which has recently been shown to be nested within the arachnids [21,22]), three Myriapoda, three Pancrustacea, and one Onychophora.…”
Section: Methodsmentioning
confidence: 99%
“…Previous efforts to decipher the higher-level relationships of sea spiders have been hindered by the omission of key lineages [11,12], inaccessibility of many families for phylotranscriptomic approaches [18,21,22], limited informativeness of legacy Sangersequenced markers [5,[11][12], compositional bias of mitochondrial genes [11], ineffectiveness of mitogenomes for resolving deep relationships of Chelicerata [13,14], and the potential for gut or epibiont contamination [5]. Here, we surmounted these challenges by integrating multiple data classes and using a target capture approach optimized for sea spider (or chelicerate) genomic sequence.…”
Section: (A) a Phylogenomic View Of Higher-level Sea Spider Relationsmentioning
confidence: 99%
“…The second concern in extrapolating developmental processes derived from pancrustaceans is that a subset of Arachnida exhibits an ancient shared genome duplication, resulting in numerous paralogs of developmental patterning genes. Recent phylogenetic and comparative genomic works on Arachnida have shown that Arachnopulmonata [ 36 38 ], the clade of arachnids that bear book lungs (e.g., spiders, scorpions, whip spiders), retain duplicates of many key transcription factors, such as homeobox genes, often in conserved syntenic blocks [ 39 42 ]. Many of the ensuing paralogs exhibit non-overlapping expression patterns and a small number have been shown to have subdivided the ancestral gene function (subfunctionalization) or acquired new functions (neofunctionalization) [ 42 – 44 ].…”
Section: Introductionmentioning
confidence: 99%